Stay with the trouble: Entangled relations – a tribute to Professor Elmarie Costandius’s embodied arts-based practice - Meiring, Kobie (Critical studies in teaching and learning, 2025)
This paper explores the pedagogical entanglements of embodiment, thinking-through-doing, and visual redress in higher education through a post-qualitative and autoethnographic approach. Engaging with the work of Professor Elmarie Costandius, I reflect on how intra-actions between students, materials, and spaces shape learning in arts-based education. Moving beyond representation, this inquiry considers how embodied arts practices disrupt entrenched binaries, allowing for more relational, emergent ways of knowing. While the discussion is situated within a specific pedagogical context, it also raises larger philosophical and global concerns about inclusive knowledge production and justice—challenging dominant modes of learning that marginalise material, affective, and embodied engagements. In doing so, this paper contributes to ongoing conversations about response-ability in arts-based education, foregrounding the ethical and epistemic stakes of making, knowing, and being in entangled pedagogical spaces.